The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1414-431x20165988
|View full text |Cite|
|
Sign up to set email alerts
|

PDK2 promotes chondrogenic differentiation of mesenchymal stem cells by upregulation of Sox6 and activation of JNK/MAPK/ERK pathway

Abstract: This study was undertaken to clarify the role and mechanism of pyruvate dehydrogenase kinase isoform 2 (PDK2) in chondrogenic differentiation of mesenchymal stem cells (MSCs). MSCs were isolated from femurs and tibias of Sprague-Dawley rats, weighing 300-400 g (5 females and 5 males). Overexpression and knockdown of PDK2 were transfected into MSCs and then cell viability, adhesion and migration were assessed. Additionally, the roles of aberrant PDK2 in chondrogenesis markers SRY-related high mobility group-box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…Normally, the MAPKs pathway consists of three signal cascades' pathway: c-Jun N-terminal kinase (JNK), p38, and extracellular signal-regulated kinase (ERK) [ 19 ]. A large number of experiments suggested that the p38 signaling pathway plays a key role in the progress of considerable human diseases, especially for the development of OA [ 20 23 ]. Activation of the p38-MAPK signaling pathway may lead to the expression of proinflammatory cytokines, chemokines, MMPs, and signaling enzymes (COX-2) in human osteoarthritis chondrocytes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the MAPKs pathway consists of three signal cascades' pathway: c-Jun N-terminal kinase (JNK), p38, and extracellular signal-regulated kinase (ERK) [ 19 ]. A large number of experiments suggested that the p38 signaling pathway plays a key role in the progress of considerable human diseases, especially for the development of OA [ 20 23 ]. Activation of the p38-MAPK signaling pathway may lead to the expression of proinflammatory cytokines, chemokines, MMPs, and signaling enzymes (COX-2) in human osteoarthritis chondrocytes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study had validated that suppressing MAPK could inhibit the differentiation of bone marrow stromal cells in a way that could upregulate expression as well as phosphorylation of both ERK and JNK . Meanwhile, Wang et al demonstrated that the expressions of both JNK and ERK increased in bone marrow mesenchymal stem cells and that MDS with hematopoietic stem cells was associated with bone marrow diseases, indicating that both JNK and ERK could be upregulated in MDS . Subsequently, cyclin was collected and promoted rapidly with the information obtained from both CDK4 and CDK6 among patients diagnosed with MDS, indicating that cyclin D, CDK4, and CDK6 are being upregulated in MDS…”
Section: Discussionmentioning
confidence: 97%
“…miR-455-3p overexpression downregulates the DNA methylation of cartilage development-related genes such as SOX6 and Smad3 . Both upregulation of SOX6 33 and Smad3 34 promotes chondrogenic differentiation of hMSCs.…”
Section: Discussionmentioning
confidence: 99%